Palaro system playground area landscape architecture rating system - Azagra, Von Gerald; Navarra, Nappy L. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
Rapid urbanization and unplanned population development can detrimental to the safety of citizens, with children being a particularly vulnerable social group. In this review, the researcher assess childhood playground related injuries and hazards and suggest mechanism which could be incorporated into playground planning. The inclusion criteria used were "children", as the focus group, "playground design" as the main field of study, and "safety" as the concepts of study. This papers accessed related articles on playground injuries and hazards, rating system and standards used in playgrounds and then, screened and reviewed systematically to come out with the theoretical framework. The result is the formulation of a rating system which sill be use to test existing playgrounds on design and safety and then, re accessed if the study is applicable for use. This study also aims to provide a comprehensive analysis and description and evaluation of playground safety design and its environmental hazards which can be brought to end users.
Includes appendices
Thesis (Master of Tropical Landscape Architecture) -- University of the Philippines Diliman